Individual Differences on Embodied Distance Estimation in Virtual Reality - Gonzalez Franco, Mar; Abtahi, Parastoo; Steed, Anthony (The 26th IEEE Conference on Virtual Reality and 3D User Interfaces, 2019)
There are important individual differences when experiencing VR setups. We ran a study with 20 participants who got a scale-matched avatar and were asked to blind-walk to a VR target placed 2.5 meters away. In such setups, people typically underestimate distances by approximately 10% when virtual environments are viewed through head mounted displays. Consistent with previous studies we found that the underestimation was significantly reduced the more embodied the participants were. However, not all participants developed the same level of embodiment when exposed to the exact same conditions.